Path Analysis: Health Belief Model Application on Predicting Oral Hygiene Behavior of Junior High School Students in Surakarta, Central Java, Indonesia - Rifda Muthia Sabrina; Eti Poncorini Pamungkasari; Bhisma Murti; Revi Gama Hatta Novika; Anik Lestari (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: The high prevalence of orodental diseases, accompanied by low prevalence of appropriate behavior in maintaining orodental health, shows the urgency of health institutions to understand the determinants influencing such behaviors in Indonesia. The aims of this study was to analyze the effect of applying the health belief model on orodental health behavior among middle school students in Surakarta. Subjects and Method: This study was a cross-sectional observational analytical quantitative study, which was conducted in 14 public Junior High Schools in Surakarta, Central Java, Indonesia from January to March 2025. The independent variables were perceived susceptibility, perceived severity, perceived benefit, perceived barrier, self-efficacy, and cues to action. Orodental health behavior acts as the dependent variable. Subjects were determined using a multistage random sampling method with a total of 210 students. The data were collected through a researcher-made questionnaire, which included questions about demographic characteristics and the six HBM constructs. Data analysis was conducted using path analysis by StataMP 13. Results: Orodental health behavior in middle school students was directly influenced by perceived benefit (OR= 0.36; CI 95%= 0.26 to 0.45; p<0.001), perceived susceptibility (OR= 0.47; CI 95%= 0.38 to 0.55; p<0.001), and self-efficacy (OR= 0.20; CI 95%= 0.10 to 0.30; p<0.001). Orodental health behavior was also indirectly influenced by perceived susceptibility and cues-to-action. Conclusion: Perceived benefit, perceived susceptibility, and self-efficacy significantly improved orodental health behavior in students.